DETERMINATION OF IDEAL CRITERIA FOR DEVELOPMENT OF SUSTAINABLE BUILDING RATING SYSTEM IN IRAN’S COLD AND DRY CLIMATE (DENA) - Elahe Nouri Segherlou; Vahid Ghobadian; Ali Asgary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Today, standards can be considered as reliable methods to be used in sustainable design of buildings. The aim of creating building rating systems is to provide a standard in the building exploitation step to be able to evaluate the building with the determined criteria. Nowadays, scoring and rating systems of sustainable buildings have been developed as a method for building environmental evaluation. On the other hand, one of the challenges for development and use of such systems is to select criteria and weight them, and no ideal instrument can be designed regardless of climatic conditions, geographical condition and special environmental priorities. Hence, regional rating system development has been welcomed significantly more than international systems. In this study, with the aim of achievement of a rating system in consistence with climatic conditions and environmental limitations of dry and cold climate, a comprehensive study is firstly conducted on available rating systems. Then, indicator portfolio and the classification of the indicators are done based on climate and the regional needs and problems. Also, for weighting purpose, indicators and sub-indicators are codified using Delphi method.